Autonomous and sectoral perception of the concept of "justice" and its relation to judicial control - Khandanyan, Rafik (Edelweiss Applied Science and Technology, 2024)
The present study delves into the complex interrelationship between the notions of "justice" and "judicial control," examining their independent and sectoral meanings both inside and outside of the Armenian legal system. Despite the fact that the terms are frequently used synonymously, this study aims to define their specific functions, especially with relation to administrative and constitutional law. The research endeavors to redefine the extent of judicial control by means of a critical analysis of Armenian constitutional provisions and a wider framework of international legal perspectives. It presents judicial control as a crucial, yet independent, function of justice. It looks at how the idea of judicial control has changed over time and the various interpretations it has received in various legal systems, drawing on historical examples. The paper examines the typologies of judicial tasks using a combination of theoretical and comparative legal techniques, highlighting important differences between jurisdictional and non-jurisdictional judicial operations. The argument for the constitutional concept of justice’s wider application than just settling legal disputes receives a lot of attention. The study shows that judicial control should be seen as a fundamental component of justice and essential to maintaining the rule of law, rather than as a secondary or auxiliary role, by looking at justice from a synoptic perspective. The article ends with helpful suggestions for improving judicial functions. It suggests that future legal changes should consider how justice is changing and how closely it is linked to judicial control in both the international and Armenian legal systems.